Supply Chain Performance and Quality Measurement of Dairy Cow Concentrate in Cooperative toward Sustainable Productivity: a Case Study - Norma Nuraina; Atikah Nur Hamidah; Despal Despal; Epi Taufik (Buletin Peternakan, 2021)
This research aims to measure supply chain performance of dairy concentrate in cooperative with the SCOR-AHP approach and develop improvement based on the performance result, and to analyze the quality suitability as a basis to develop a comprehensive quality standard and its quality control mechanism. This research was conducted at a dairy farmer cooperative located in West Java. The analysis used to measure the performance was supply chain operation reference-analysis hierarchy process (SCOR-AHP). For measuring the product quality, ten post-production concentrate samples, 27 samples after the distribution process, and 25 samples for homogeneity test from five mixer machines were taken. Concentrate quality parameters were moisture, ash, crude fat, crude protein, crude fiber, total digestible nutrients (TDN), and salt content. Post-production samples data were compared with Indonesian National Standard (SNI) using one-tailed one-sample t-test, samples data from the field were tested using two samples independent t-tests compared to post-production samples data, and homogeneity test was seen from the coefficient of variation value of the salt content. The results show that the supply chain performance value of dairy cow concentrate at the cooperative is excellent. The nutrient content complies with SNI, but the homogeneity of the mixture is classified as poor category. The nutrient content of samples taken from the field shows differences with post-production samples except for TDN. The excessive total cost can be utilized to enhance performance in generating a better quality product. The cooperative should enhance homogeneity by concerning the mixing process and maintain the quality consistency by reformulating, stabilizing the quality of feedstuff, and calculating stock properly to avoid longer storage.